HUBUNGAN KENYAMANAN DENGAN EKONOMI KESEHATANPADAPASIENBPJS KESEHATANDIRUANG RAWAT INAP RSUD ARIFIN ACHMAD PROVINSI RIAU - Refila Fazira; Bobi Handoko, Abdul Zaky, Marian Tonis (Jurnal Kesehatan, 2024)
Health financing still relies heavily on private money, causing most of the population to be less protected. The purpose of this study was to determine the relationship between patient comfort and BPJS health economy in the inpatient room of Arifin Achmad Hospital, Riau Province. This study was conducted using quantitative method with Cross Sectional research design. The sample in this study were patients or families of inpatients participating in the Health BPJS who did not upgrade the class of inpatient room nurses at Arifin Achmad Hospital in 2022. Sampling in this study used Non-Probability Sampling technique. The dimensions of service quality evaluated include Tangible, Reability, Responsiveness, Assurance, and Emphaty. The results show that income and education have a significant relationship with most dimensions of service quality, including Tangible, Reability, Assurance, and Emphaty. However, the number of family members is not significantly related by Responsiveness and Assurance variables. To determine the relationship of inpatient room patient comfort to health economics. The subjects in this study were BPJS Health patients in the inpatient room. The object of this study, the relationship of patient comfort to service quality which includes Tangibles (tangible form), Reability (reliability), Responsiveness (readiness), Assurance (guarantee), and Emphaty (empathy) to the Health Economy. In this study, the results of the assessment of respondents regarding each indicator on the health economy and service quality variables were obtained.